Delivering pharmacogenetic testing in a primary care setting - Mills R; Voora D; Peyser B; Haga SB (Dove Medical Press, 2013)
Rachel Mills,1 Deepak Voora,1,2 Bruce Peyser,3 Susanne B Haga1,2 1Duke Institute for Genome Sciences and Policy, 2Duke Center for Personalized and Precision Medicine, 3Duke University Medical Center, Pickett Road Primary Care Clinic, Duke University, Durham, NC, USA Abstract: Pharmacogenetic testing refers to a type of genetic test to predict a patient's likelihood to experience an adverse event or not respond to a given drug. Despite revision to several labels of commonly prescribed drugs regarding the impact of genetic variation, the use of this testing has been limited in many settings due to a number of factors. In the primary care setting, the limited office time as well as the limited knowledge and experience of primary care practitioners have likely attributed to the slow uptake of pharmacogenetic testing. This paper provides talking points for primary care physicians to discuss with patients when pharmacogenetic testing is warranted. As patients and physicians become more familiar and accepting of pharmacogenetic testing, it is anticipated that discussion time will be comparable to that of other clinical tests. Keywords: pharmacogenetics, primary care, pharmacogenetic testing, patient education